Five decades of the Fontan operation: A systematic review of international reports on outcomes after univentricular palliation. (25th January 2018) - Kverneland, Laura S.; Kramer, Peter; Ovroutski, Stanislav
Abstract: Almost fifty years after its first clinical application, the modified Fontan operation is among the most frequently performed procedures in congenital heart disease surgery in children today. The objective of this review is to systematically summarize the international evolution of outcomes in regard to morbidity and mortality of patients with Fontan palliation. All studies published over the past five decades with more than 100 Fontan patients included were screened. In eligible studies, information concerning preoperative patients' characteristics, Fontan modifications employed, early mortality, long‐term survival and frequency of relevant complications was extracted. Ultimately, thirty‐one studies published by the largest surgical centers with an overall number of 9390 patients were included in this review. The extracardiac total cavopulmonary anastomosis is the most frequently used Fontan modification. Hemodynamic data demonstrate a rigorous overall adherence to suggested Fontan selection criteria. The analysis showed a clear trend toward improved early and long‐term survival over the time period covered. Although inconsistently reported, severe complications such as arrhythmias, thromboembolic events and protein‐losing enteropathy as well as reoperations and reinterventions were frequent. In conclusion, patients palliated for complex univentricular heart malformations nowadays benefit from the experience and technical developments of the past decades and have a significantly improved long‐term prognosis. However, important issues concerning postoperative long‐term morbidity and mortality are still unsolved and clear intrinsic limitations of the Fontan circulation are becoming evident as the population of Fontan patients ages.